Evaluasi Pembelajaran Pendidikan Agama Islam dalam Penilaian Sikap dan Nilai di Madrasah Ibtidaiyah Miftahul Ulum 5 Congkop - Abdullah; Moh. Nurullah; Ali Ridho (Jurnal Ilmiah Multidisiplin Mahasiswa dan Akademisi, 2026)
This study aims to describe the implementation of Islamic Religious Education learning evaluation in assessing students' attitudes and values at MI Miftahul Ulum 5 Congkop, identify supporting and inhibiting factors, and analyze efforts to improve the quality of the evaluation system. This research employed a qualitative descriptive approach. The participants consisted of the principal, Islamic Religious Education teachers, and students from grades IV to VI. Data were collected through observation, in-depth interviews, and documentation, and analyzed using the Miles, Huberman, and Saldaña interactive model, including data reduction, data display, and conclusion drawing. Data validity was ensured through source and method triangulation. The findings indicate that the evaluation of Islamic Religious Education learning has implemented authentic assessment integrating cognitive, affective, and psychomotor domains. Attitude assessment was conducted through observation, teacher journals, self-assessment, and peer assessment focusing on students' spiritual and social attitudes. Supporting factors included teachers' commitment, principal supervision, a religious school culture, and parental involvement. Inhibiting factors consisted of limited instructional time, large class sizes, manual assessment administration, and inconsistent documentation of students' attitude development. Improvement efforts involved academic supervision, teacher professional development, refinement of assessment instruments, simplification of assessment journals, and the planned implementation of digital-based assessment systems. The study concludes that the evaluation system has been implemented effectively; however, improvements in assessment instruments, teacher competence, documentation consistency, and digitalization are necessary to enhance the objectivity, effectiveness, and sustainability of attitude and values assessment.